Natural Pigment from Madder Plant as an Eco-Friendly Cathode Material for Aqueous Li and Na-Ion Batteries. Issue 10 (27th October 2021) - Sencanski, Jelena; Nikolić, Nenad; Nedić, Zoran; Maksimović, Jelena; Blagojević, Stevan; Pagnacco, Maja
Abstract : Modifying commercial Li-ion batteries to become more environmentally friendly is of a growing concern. This paper provides an examination of a potential replacement for commercial cathode material using a naturally occurring purpurin in aqueous solutions of lithium and sodium salts. The purpurin is extracted from the Madder plant ( Rubia tinctorum ) and characterized through XRPD, FTIR, and SEM methods. The intercalation and de-intercalation capacities obtained for the purpurin as a cathode material in the aqueous solution of LiNO3 are approximately 40 mAh g −1 . Compared to the capacity of ∼35 mAh g −1 obtained for commercially used transition metal oxides in an aqueous solution of Li salt, results presented make the purpurin a promising material for the "green" development of Li-ion batteries. Although the initial purpurin capacity in NaNO3 solution is almost doubled (∼73 mA h g −1 ) compared to that of Li-salt, it is unstable and fades during cycling. The possible explanation of the electrochemical behavior of purpurin as the cathode material in aqueous solutions of Li and Na salts is discussed in detail.